524 Tim-4+ resident macrophages impair anti-tumor immunity in the serous body cavities By sequestering viable and cytotoxic CD8+ T cells expressing high levels of phosphatidylserine. (10th December 2020) - Chow, Andrew; Schad, Sara; Green, Michael; Hellmann, Matthew; Ceglia, Nicholas; Allaj, Viola; Zago, Giulia; Shah, Nisarg; Sharma, Sai; Mattar, Marissa; Chan, Joseph; Rizvi, Hira; et al.
Abstract : Background: Malignant pleural effusions and peritoneal carcinomatosis are associated with poor outcomes in patients with cancer. 1–3 Macrophages in these serous body cavities express the phosphatidylserine receptor Tim-4. 4–8 Prior reports demonstrated that Tim-4 abrogation is associated with improved anti-tumor activity. 9–11 Whether macrophages expressing Tim-4 contribute to immunosuppression in the serous body cavities has not been previously investigated. Methods: We retrospectively annotated sites of metastases in 500 patients with lung cancer and assessed for clinical outcomes. Utilizing a combination of flow cytometry, immunohistochemistry, and antibody biodistribution assays, we surveyed for Tim-4 expression across various tissues and cell types. We performed flow cytometry on 55 consecutive pleural and peritoneal effusions from patients with lung cancer. We utilized murine models of peritoneal carcinomatosis to determine whether Tim-4 abrogation could enhance the anti-tumor efficacy of anti-PD-1 therapy. We characterized CD8+ T cells with high levels of phosphatidylserine (PShigh) with flow cytometry, cytotoxicity assays, and paired single cell RNA and TCR sequencing. Confocal microscopy was utilized to visualize interactions between Tim-4+ macrophages and PShigh CD8+ T cells. Results: Metastatic disease involvement of the pleural or peritoneal cavity was associated with reduced response rate and progression-free and overall survival. We demonstrate that Tim-4 is highly expressed on pleural and peritoneal macrophages and other select resident macrophages, but not on monocytes, tumor-associated macrophages, or tumor cells in mice and humans. High levels of Tim-4 on macrophages from fluid biospecimens is associated with reduced levels CD39+ CD8+ T cells, which comprise the tumor-reactive portion of CD8+ T lymphocytes. In order to further elucidate the mechanism of Tim-4+ macrophage-mediated immunosuppression, we established a murine model of peritoneal carcinomatosis with MC38 and CT26 colon carcinoma. Genetic or pharmacologic abrogation of Tim-4 improved the efficacy of anti-PD-1 therapy and was associated with enhanced CD39+ CD8+ T cell numbers. In parallel, we observed in mice and humans that CD8+ T cell activation results in PS upregulation despite not undergoing cell death. PShigh CD8+ T cells expressed genes associated with cytotoxicity, activation/exhaustion, and proliferation, and mediated greater cytotoxicity. Mechanistic studies revealed that Tim-4 mediates sequestration of PShigh CD8+ T cells by macrophages which subsequently impedes CD8+ T cell cytotoxicity of tumor cells. Conclusions: We demonstrate that Tim-4+ resident macrophages impair anti-tumor CD8+ T cell immunity in the serous body cavities and Tim-4 blockade represents on a novel therapeutic strategy to overcome resistance to immune checkpoint blockade (figure 1 ). Ethics Approval: The retrospective clinical analysis was approved by Memorial Sloan Kettering Cancer Center IRB #16-1566. The human biospecimen analyses were approved by Memorial Sloan Kettering Cancer Center IRB #06-107 and 14-091. References: Porcel JM, et al., Clinical features and survival of lung cancer patients with pleural effusions. Respirology 2015;20 :654–659. Donnenberg AD, Luketich JD, Dhupar R, Donnenberg VS. Treatment of malignant pleural effusions: the case for localized immunotherapy. J Immunother Cancer 2019;7 :110. Morano WF, et al., Intraperitoneal immunotherapy: historical perspectives and modern therapy. Cancer Gene Ther 2016;23 :373–381. Bain CC, et al., Long-lived self-renewing bone marrow-derived macrophages displace embryo-derived cells to inhabit adult serous cavities. Nat Commun 2016;7:ncomms11852. Wong K, et al., Phosphatidylserine receptor Tim-4 is essential for the maintenance of the homeostatic state of resident peritoneal macrophages. Proc Natl Acad Sci U S A 2010;107 :8712–8717. Miyanishi M, et al ., Identification of Tim4 as a phosphatidylserine receptor. Nature 2007;450 :435–439. Rodriguez-Manzanet R, et al . T and B cell hyperactivity and autoimmunity associated with niche-specific defects in apoptotic body clearance in TIM-4-deficient mice. Proc Natl Acad Sci U S A 2010;107 :8706–8711. Kobayashi N, et al . TIM-1 and TIM-4 glycoproteins bind phosphatidylserine and mediate uptake of apoptotic cells. Immunity 2007;27 :927–940. LD Cunha et al . LC3-Associated phagocytosis in myeloid cells promotes tumor immune tolerance. Cell 2018;175 :429–441 e416. Baghdadi M, et al, TIM-4 glycoprotein-mediated degradation of dying tumor cells by autophagy leads to reduced antigen presentation and increased immune tolerance. Immunity 2013;39 :1070–1081. Baghdadi M, et al . Combined blockade of TIM-3 and TIM-4 augments cancer vaccine efficacy against established melanomas. Cancer Immunol Immunother 2013;62 :629–637.